Socially desirable responding in personality assessment: Is it possible to measure (only) lying? - Galić, Zvonimir (2008)
The poster deals with the nature of socially desirable responding and methods for its measurement. The results of two studies testing models of socially desirable responding that distinguish between deliberate impression management and unconscious self-deception are presented.